Evaluation of Higher-Order Thinking Skills of Middle School Students on Vibration and Wave Topic Using Rasch Measurement - Annur Indra Kusumadani; Harry Afandy; Lina Agustina; Rina Astuti; Muhamad Waluyo (Postgraduate, University of Mataram, 2025)
Higher-order thinking skills (HOTS) are crucial in science education, yet students often struggle to master them, particularly in complex topics such as vibrations and waves. This study aimed to evaluate the HOTS performance of 165 eighth-grade students from five schools in Purbolinggo Sub-district, East Lampung, using a two-tier multiple-choice test analyzed through the Rasch Measurement Model. The test consisted of 12 items, each with a content question and a reasoning tier, adapted from Treagust (1988) and validated through expert judgment. Rasch analysis indicated that most students demonstrated low HOTS ability, especially in the creating domain (C6), involving generating novel ideas or solutions. In contrast, analyzing (C4) and evaluating (C5) were relatively easier but still reflected limited mastery. The highest difficulty appeared in questions requiring divergent thinking and complex synthesis. Item fit statistics showed good instrument validity (person reliability = 0.93; item reliability = 0.83). These findings highlight the importance of implementing learning strategies that foster creativity and synthesis, such as problem-based learning or project-based approaches. The study was limited to one geographic area, which may restrict generalizability. Future research should explore broader contexts and incorporate qualitative data to deepen understanding of HOTS development in science.